Educational interventions to improve maternal‐foetal outcomes in women with gestational diabetes - Gorbán de Lapertosa, Silvia (2021)
To evaluate improvement in gestational diabetes (GDM) outcomes for mothers and their offspring induced by education provided to the healthcare team (HCTM) and women with GDM, plus coordination between primary care units (PCU) and highly complex maternity (HCM) facilities.